A Review on Trends of Food Supply and Nutrient Intake in the Republic of Korea over the Past 30 Years - Kim, Jong-Gyu; Kim, Joong-Soon; Kim, Jeong-Gyoo (Current Research in Agricultural and Food Science Vol. 5, 2021)
Purpose: This study was conducted to investigate food supply and consumption trends in the Republic of Korea (South Korea) over the past 30 years (1980 to 2010). Methods: We used time series data on Food Balance Sheets of Korea and National Health and Nutrition Survey from Statistics Korea. Regression analysis was performed for trends of food supply and demand, and t-test for gender difference in nutrient intake. Results: The annual supply of cereals, rice and starch roots per person has decreased, while that of meat, fish and shellfish, eggs, milk, and fats and oils has increased (p < 0.05), respectively. These changes effect on nutrient intake: rice consumption has declined to one thirds of total energy intake, however the energy intake from lipid sources has increased up to 20% in 2000s. The nutrient intake levels are mostly sufficient to meet the recommended intake, but calcium intake is below the recommended level and sodium is three times above the recommended level. These problems are found in both genders, and males take in more calories and sodium than females (p < 0.05). Conclusion: These changes in food consumption and supply resulted in lowering both quantity based food self-sufficiency rate and self-sufficiency of nutrition supply. It is therefore suggested that the supply of agricultural products should be stable and quality competitiveness in supply should be improved. Also measures and strategies in promoting rice consumption are required, such as promoting healthy diet via nutrition education, and disseminating healthy traditional Korean food. On a consumption side, we should raise awareness of consumption of agricultural products in Korea promoting healthy diets via nutrition education, and disseminating healthy traditional Korean food. We believe that through such efforts and promotion it will be possible to strengthen food security, to preserve traditional dietary pattern, and to maintain the health of Korean people.